1981
DOI: 10.1073/pnas.78.11.6917
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-induced receptor loss in cultured human lymphocytes is due to accelerated receptor degradation.

Abstract: We have measured the turnover rate ofthe polypeptide subunits of the insulin receptor in cultured human lymphocytes (IM-9 line) and have investigated the mechanism of insulin-induced receptor loss. To estimate the rate of receptor degradation, lymphocytes were either pulse-labeled with [asSimethionine or surface labeled with NaF4 and lactoperoxidase. The insulin receptor was isolated by immunoprecipitation with anti-receptor antibody, and the rate of loss of radioactivity from each receptor subunit was determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
107
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(117 citation statements)
references
References 31 publications
9
107
1
Order By: Relevance
“…However, these authors (Krupp and Lane, 1981 ;Standaert and Pollet, 1984) used cells cultured with insulin for a long period of time while, in the present study, this hormone was acutely administered. Therefore, although insulin exposure can be said to accelerate the degradation rate of its receptors in some cell lines (Kasuga et al, 1981 ;Knutson et al, 1983;Okabayashi et al, 1989), this does not seem to represent a general mechanism for hormone-induced down-regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these authors (Krupp and Lane, 1981 ;Standaert and Pollet, 1984) used cells cultured with insulin for a long period of time while, in the present study, this hormone was acutely administered. Therefore, although insulin exposure can be said to accelerate the degradation rate of its receptors in some cell lines (Kasuga et al, 1981 ;Knutson et al, 1983;Okabayashi et al, 1989), this does not seem to represent a general mechanism for hormone-induced down-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The level of down-regulation in these cells is determined by the dynamic equilibrium between receptor internalization and recycling rates. However, in other cell types, downregulation has been associated with an increased rate of receptor inactivation or degradation (Kasuga et al, 1981;Knutson et al, 1983;Okabayashi et a]., 1989).…”
mentioning
confidence: 99%
“…For several growth factors like insulin, epidermal growth factor or platelet-derived growth factor, it has been shown that, after binding, the respective receptors are internalized and down-regulated [19][20][21][22][23]. In the present study we have investigated the fate of the hepatic IL6-receptor and its ligand after their interaction.…”
Section: Discussionmentioning
confidence: 99%
“…In (Goldstein et al, 1979;Karin and Mintz, 1981). Endocytosis is also used to internalize hormnone-and growth factor-receptor complexes and to direct them to lysosomes 1865 for destruction after signal transmittance (Carpenter and Cohen, 1976;Kasuga et al, 1981). It is not clear how the yeast cell makes use of its endocytotic capacity.…”
Section: Introductionmentioning
confidence: 99%